Pelvic fracture-related hypotension: A review of contemporary adjuncts for hemorrhage control. Issue 4 (8th October 2021) - DuBose, Joseph J.; Burlew, Clay Cothren; Joseph, Bellal; Keville, Meghan; Harfouche, Melike; Morrison, Jonathan; Fox, Charles J.; Mooney, Jennifer; O'Toole, Robert; Slobogean, Gerard; Marchand, Lucas S.; Demetriades, Demetrios; et al.
Abstract : ABSTRACT: Major pelvic hemorrhage remains a considerable challenge of modern trauma care associated with mortality in over a third of patients. Efforts to improve outcomes demand continued research into the optimal employment of both traditional and newer hemostatic adjuncts across the full spectrum of emergent care environments. The purpose of this review is to provide a concise description of the rationale for and effective use of currently available adjuncts for the control of pelvic hemorrhage. In addition, the challenges of defining the optimal order and algorithm for employment of these adjuncts will be outlined. LEVEL OF EVIDENCE: Review, level IV.